Dual viscosity mixture vehicle for intratympanic steroid treatment modifies the ROS and inflammation related proteomes - Jung, Jin Woo; Li, Hui; Lee, Jung Hun; Hwang, Yu-Jung; Dan, Kisoon; Park, Moo Kyun; Han, Dohyun; Suh, Myung-Whan (Frontiers in Pharmacology, 2023)
Until recently, the most standard treatment for sensorineural or sudden hearing loss, which is caused by inner ear damage or deterioration, has been systemic oral steroid administration. In recent, intratympanic steroid injections such as dexamethasone have been used for the treatment of sudden hearing loss as well. It is injected into the tympanic cavity through its membrane and is expected to diffuse over the round window located between the tympanic cavity and the inner ear. However, in clinical situations, the delivery time of steroids to the inner ear is shorter than 24 hours, which does not allow for a sufficient therapeutic effect. Therefore, we applied a previously invented dual viscosity mixture vehicle (DVV) for intratympanic dexamethasone to a guinea pig model, which could reduce the side effects of systemic steroid administration with sufficient dwelling time for the treatment of hearing loss, and we investigated the physiological changes with a global proteomic approach. In this study, we extracted perilymph in three different conditions from guinea pigs treated with dexamethasone-embedded DVV, dexamethasone mixed in saline, and control groups to compare proteomic changes using tandem mass spectrometry analysis. After liquid chromatography coupled tandem mass spectrometry (LC-MS/MS) analysis, we first identified 46 differentially expressed proteins (DEPs) that were statistically significant after an ANOVA multiple-sample test. We also performed pairwise comparisons among each group to identify DEPs closely related to the treatment response of dexamethasone-embedded DVV. Gene ontology enrichment analysis showed that these DEPs were mostly related to inflammation, immune, actin remodeling, and antioxidant-related processes. As a result, the proteome changes in the DVV-treated groups revealed that most upregulated proteins activate the cell proliferation process, and downregulated proteins inhibit apoptosis and inflammatory reactions. Moreover, the reactive oxygen process was also regulated by DEPs after DVV treatment.